Treatment of water hyacinth and pineapple indigenous fibers for textile applications using plasma enhanced chemical vapor deposition (PECVD) - Aleño, Jay-Anne B. (2013)
The effects of plasma treatment on chemical and physical properties of indigenous fibers such as water hyacinth and pineapple were investigated. Oxygen, argon, hydrogen and mixed oxygen/argon gases were used to produce plasma in a plasma-enhanced chemical vapor deposition device. A design of experiment using three-factorial analysis was used to optimize the parameters namely: type of gas, discharge potential, pressure, and treatment time. Yarns were produced from the plasma treated indigenous fibers with 80% polyester, 10% water hyacinth and 10% pineapple composition and were characterized using Raman spectroscopy, atomic force microscopy (AFM), Fourier transform infrared analysis (FTIR) and tensile strength. Properties of textiles made from yarns were further characterized by scanning electron microscopy fitted with energy dispersive x-ray (SEM-EDX), x-ray diffraction analysis (XRD), thermogravimetric analysis (TGA), contact angle, dyeability, air permeability, color quality thru percent reflectance, and laundering. Results show that textiles made from plasma treated indigenous fibers such as water hyacinth and pineapple possess comparable properties of commercial 100% polyester textiles.